Early Detection of Degenerative Diseases in the Elderly in Uenuni Village, Palolo District - Yuliet Yuliet; Khildah Khaerati; Amelia Rumi; Khusnul Diana (Warta Pengabdian Andalas)
The risk of various degenerative diseases is more experienced by older adults than young people. One of the most common health problems among the elderly is hypertension. Delays in treating hypertensive patients are caused by the majority of patients only coming to health facilities after experiencing complications and lack of access to public health services. The incidence of dyslipidemia and diabetes mellitus (DM) also continues to grow, which are risk factors for coronary heart disease. For this reason, promotive and preventive efforts for the elderly group are significant through increasing knowledge and understanding of degenerative diseases. The community service partner is the Banpres Pololo Community Health Center, one of the community health centers in Sigi Regency with high cases of degenerative diseases, and the target of community service is the elderly in Uenuni Palolo village. Implementing the activity was health education about hypertension, DM, and dyslipidemia, health screening, and health counseling. The screening results found that 94.12% of older adults suffered from hypertension, 17.65% suffered from DM, and 52.94% suffered from hypercholesterolemia. Health counseling results show that most older adults did not understand the importance of early detection of degenerative diseases. Therefore, health education and counseling for the community still need to be improved.